Conceptualization and operationalization of empathy in design research - Surma-aho, Antti; Hölttä-Otto, Katja (Design studies, 2022)
In this research note, we bring clarity to the concept of empathy in design research by discussing issues in its conceptualization and operationalization. We review literature to identify and clarify the core concepts of empathy and to showcase its potential operationalizations, borrowing from closely related fields of social psychology and neuroscience. We identify five core concepts: empathic understanding, empathic design research, empathic design action, empathic orientation, and empathic mental processes. We also identify six potential operationalizations: empathic tendencies, beliefs about empathy, emotion recognition, understanding mental contents, shared feelings, and prosocial responding. By combining the core concepts and operationalizations, we provide a frame of operation for future empathy research in design. •Core concepts of empathy in design are proposed to clarify its definition.•Empirical indicators for empathy are reviewed to support future research.•Many identified empirical indicators are not directly applicable in the design context.•Our review and conceptual clarification provide basis for transparent scientific discourse.